2023
DOI: 10.1177/11206721231166434
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal imaging in Best Vitelliform Macular Dystrophy: Literature review and novel insights

Abstract: Best Vitelliform Macular Dystrophy (BVMD) is a dominantly inherited retinal disease caused by dominant variants in the BEST1 gene. The original classification of BVMD is based on biomicroscopy and color fundus photography (CFP); however, advancements in retinal imaging provided unique structural, vascular, and functional data and novel insights on disease pathogenesis. Quantitative fundus autofluorescence studies informed us that lipofuscin accumulation, the hallmark of BVMD, is unlikely to be a primary effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Additionally, the thickness of the ONL above the vitelliform lesions was correlated to retinal sensitivity. A similar study by Bianco et al 17 hypothesized that vitelliform lesions in Best vitelliform macular dystrophy resulted from lack of apposition of photoreceptors and RPE. This led to subretinal accumulation of shed photoreceptor outer segments, photoreceptor degeneration, and subsequent loss of retinal sensitivity.…”
Section: Discussionmentioning
confidence: 88%
“…Additionally, the thickness of the ONL above the vitelliform lesions was correlated to retinal sensitivity. A similar study by Bianco et al 17 hypothesized that vitelliform lesions in Best vitelliform macular dystrophy resulted from lack of apposition of photoreceptors and RPE. This led to subretinal accumulation of shed photoreceptor outer segments, photoreceptor degeneration, and subsequent loss of retinal sensitivity.…”
Section: Discussionmentioning
confidence: 88%
“…Malfunctioning of this chloride channel, situated on the basolateral membrane of RPE cells, results in the subretinal accumulation of lipofuscin and unphagocytosed photoreceptor outer segments [93]. Clinically, this condition is marked by the characteristic "egg yolk" (vitelliform) macular lesion and a reduced Arden ratio (<1.5) on electrooculogram [94]. Although the original classification relied on fundus examination and photography, recent advances in retinal imaging have deepened our understanding of BVMD pathophysiology, leading to more accurate diagnosis and the development of novel staging systems [95][96][97][98].…”
Section: Best Vitelliform Macular Dystrophymentioning
confidence: 99%
“…OCT imaging is also useful to depict the last stage of BVMD with fibrosis, atrophy, scarring, and/or macular neovascularization. Therefore, OCT B-scans can display and differentiate each of the stages of the BVMD, and are useful for the longitudinal monitoring of the disease [122][123][124][125]. Several studies have suggested that progressive enlargement of the area of EZ loss is associated with greater BCVA deterioration [126].…”
Section: Best's Disease (Bd)/best Vitelliform Macular Dystrophy (Bvmd)mentioning
confidence: 99%